Utilization of Clustering and TOPSIS Method for Selecting Suppliers with Supply’s Limitation - Ramin Sadeghian; Mahmood Masnadjam (مدیریت تولید و عملیات, 2015)
Generally supply chain's investigation has two basic problems. The first problem occurs when the number of suppliers, products and items are very much. Nowadays, due to the complexity of production systems, the suppliers have some limitations. This is the second problem. One of the constraints is that the demands should be completely met by suppliers. In this paper, the mentioned problem is solved by clustering both items and suppliers, and also applying TOPSIS model. The proposed method is performed on a production plant as a case study also the obtained results are compared with the results of DEA method. The results of both methods are the same.